Socioeconomic and contextual correlates of suicidal ideation among Indonesian adults: Evidence from a multilevel analysis of the 2018 National Health Survey - Sujarwoto Sujarwoto; Penny Bee; Helen Brooks; Asri Maharani (PLoS ONE, 2026)
Suicide is a major public health concern and a leading cause of premature death, particularly in low- and middle-income countries. In Indonesia, the true burden is likely underestimated due to stigma and underreporting. Evidence on suicidal ideation, an important precursor to suicide, remains limited. This study aims to identify individual and community correlates of persistent suicidal ideation among Indonesian adults using nationally representative data. A cross-sectional analysis was conducted using data from the 2018 Indonesia National Health Survey covering adults aged 18 years and older. District-level indicators were obtained from the 2018 Village Potential Statistics and regional economic data from the National Bureau of Statistics. Multivariable and multilevel logistic regression models identified individual and contextual factors associated with suicidal ideation, accounting for individuals nested within districts. Among 636,285 adults (mean age 42.5 years; 47.4% female), 0.87% reported persistent suicidal ideation in the past month. Higher community social capital (OR = 0.94; 95% CI 0.88–1.00) and district GDP (OR = 0.91; 95% CI 0.86–0.97) were associated with lower odds, while social deprivation increased risk (OR = 1.13; 95% CI 1.06–1.21). Lower odds of suicidal ideation were observed among women (OR = 0.56), married (OR = 0.65) or widowed individuals (OR = 0.77), those with higher education attainments (OR = 0.32 for university graduates), and resident of Java (OR = 0.61). Divorce (OR = 1.28), older age (OR = 1.83 for ages 65–74), chronic illness (OR = 1.56 for heart disease), and poor self-rated health (OR = 3.38) were linked to higher risk. Strengthening community social capital and reducing social deprivation are vital to prevent suicidal ideation in Indonesia. Interventions should address socioeconomic inequalities and improve access to health and social support, especially among older adults and those with chronic illness. Promoting inclusive economic growth and community resilience may help mitigate the underlying stressors contributing to suicidal thoughts.